Phytochemical study of Artocarpus gomezianus wall. ex trec. leaves - Benjaporn Kingroungpet; Chulalongkorn University. Graduate School (Chulalongkorn, 2013)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1994